Pengaruh Net Profit Margin, Return On Equity dan Earning Per Share Terhadap Harga Saham Perusahaan Sektor Energi: Studi pada Perusahaan Bursa Efek Indonesia Periode 2018-2022 - Satriaji Vinatra; LiA Nirawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The capital market serves as a platform for the trading of long-term financial instruments to businesses or governments seeking funding for expansion and development, particularly in this study, equities (stocks). This research aims to investigate the impact of stock price fluctuations within the energy sub-sector, which is comparatively higher than most other sectors. To achieve this, the researcher utilizes profitability ratios, namely Net Profit Margin (NPM), Return On Equity (ROE), and Earnings Per Share (EPS), concerning the stock prices of companies within the energy sub-sector listed on the Indonesia Stock Exchange (BEI) during the period from 2018 to 2022. This study adopts a quantitative descriptive approach, with a population of 74 companies. Multiple Linear Regression is employed as the data analysis technique. Based on the results of the F-test analysis, the computed F-value is 3.962, surpassing the critical F-value of 3.08, indicating that NPM, ROE, and EPS collectively influence the stock prices of the energy sub-sector listed on the BEI from 2018 to 2022. Meanwhile, the t-test results reveal respective t-values for NPM, ROE, and EPS as 1.020, -1.244, and 2.779, against a critical t-value of -1.982 and 1.982. Consequently, only EPS exhibits partial influence on stock prices, whereas NPM and ROE do not exert partial influence on the stock prices of the energy sub-sector listed on the BEI during the period from 2018 to 2022.